Immunoreactivity of the 14F7 Mab (Raised against N-Glycolyl GM3 Ganglioside) as a Positive Prognostic Factor in Non-Small-Cell Lung Cancer. (26th February 2012) - Blanco, Rancés; Rengifo, Charles E.; Cedeño, Mercedes; Frómeta, Milagros; Rengifo, Enrique; Carr, Adriana
Abstract : Lung carcinoma is the leading cause of cancer-related mortality worldwide. Therefore, numerous studies are focusing on the assessment of other biological and molecular prognostic factors in these tumors. We evaluated the relationship between 14F7 Mab reactivity, pathological features, DNA-content and S-phase fraction (SPF), and their impact in the survival of NSCLC patients. Hematoxylin and eosin staining and immunohistochemistry optical microscopy assays as well as DNA content and SPF measuring using flow cytometry were performed. The 14F7 reactivity was widely observed in NSCLC sections, no depending of the clinicopathological characteristics. We also obtained differences in the intensity of reaction with 14F7 as well as in the SPF between diploid and aneuploid carcinomas. Patients with diploid tumors showing higher SPF and 14F7 reaction joint to a low mitotic index displayed higher survival rates. Our results are in agreement with the assumption of the possible positive prognostic value of 14F7 staining in NSCLC.